'The sequential organisation of gossip talk'. (August 2021) - Aslan, Tugba
Gossip, in its most general sense, means talking about absent third parties with regards to their strengths and weaknesses in an evaluative or informative tone. It is a common phenomenon and has been investigated from different perspectives of research such as human sciences, behavioural psychology, anthropology and so forth. Although it is a prevalent research topic amongst researchers of various disciplines, the sequential organisation of gossip talk still keeps its authenticity in terms of real-life talk-in-action research. This study aims to provide a micro-analysis of the sequential organisation of gossip talk adopting an emic perspective. The data set consists of a collection of 90 hours of audio data collected from a retirement home in Turkey. The data are analysed using Conversation Analysis. The results of the micro-analysis of authentic gossip talk points to a systematicity in gossip talk sequences in terms of initiation, response and closing.